Efektivitas Pelaksanaan MBS Dalam Peningkatan Mutu Pembelajaran - Ramli Yusuf (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2016)
School management  is one of  the affect the quality of education, it can even determine the effectiveness of the curriculum, a variety of learning  tools, teaching  time and learning process. The concept of school based management  was first known in the United States. When questioned school to service  the  needs of  the public. The Performance of educational institutions  failing  for  prepare  or produce graduates who are not in accordance with the demands and needs of the workforce, especially in the face of  global economic dynamics increasingly competitive. This  phenomenon  is encouraging people  and  government   to take a strategic and anticipatory to  reform school by improving returns management